Faktor-Faktor yang Memotivasi Perempuan Berpendidikan Tinggi (Studi Kasus pada Perempuan Batak Toba di Kota Bandung) - Denada Ferita Sihite; Achmad Hufad; Siti Nurbayani (Jurnal Paedagogy, 2022)
This study aims to reveal the factor that motivates the higher-educated Toba Batak women. The research used a qualitative approach. Purposive sampling was employed to choose the study's participants, who are Toba Batak women from Bandung city with advanced degrees. The study employed guidelines for observation and interviewing as data collecting methods. The data reduction, data display, and conclusion drawing techniques used in this study were based on the interview transcripts. The results of this study indicate that the factors that cause Toba Batak women to have higher education include: (1) mindset and value changes, (2) need for time demand, (3) women's choices, and (4) family support.